TUNDA ISLAND AS A TOURIST ATTRACTION IN TIRTAYASA DISTRICT, SERANG REGENCY - Chotibul Umam; Evi Novianti (JELAJAH: Journal of Tourism and Hospitality, 2021)
The lack of research related to the potential for tourist attraction of Tunda Island from natural, artificial, cultural, and various other aspects based on existing conditions, is the urgency of this research. Tourist visits that are still fluctuating require special attention from the Serang Regency Government to optimize development. Therefore, this study's purpose is to identify the existing conditions and tourism potential of Tunda Island. Thus it can become a guideline for decision-making related to the tourism development in Tunda Island in the future. This research used qualitative research methods with a case study design. By purposive sampling, informants who are the community and tourism managers of Tunda Island were selected for in-depth interviews. The proportion of the results of this study was also more inclined to the field observations to achieve the research objectives. Secondary data came from literature studies related to previous research and also document studies from data to Tunda Island. The results showed that the potential of Tunda Island as a tourist attraction has the opportunity or the potential for natural or marine tourism. However, the potential cultural tourism attractions, both tangible and intangible, also need to be packaged and raised as a tourist attraction based on local potential. Also found in the potential for an artificial tourist attraction that can support tourism on Tunda Island. In the end, the results of this study expected to become input for the Serang Regency Government and other stakeholders to develop tourism activities that are relevant and able to integrate cultural, natural, and artificial tourism attractions.